The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11469-014-9487-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Depression on Driver Performance

Abstract: Always cite the published version, so the author(s) will receive recognition through services that track citation counts, e.g. Scopus. If you need to cite the page number of the TSpace version (original manuscript or accepted manuscript) because you cannot access the published version, then cite the TSpace version in addition to the published version using the permanent URI (handle) found on the record page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 56 publications
4
36
0
1
Order By: Relevance
“…at leads to the ability of multiobject tracking, becoming an important predictor of job performance just as the similar job of air traffic controllers [30]. e result that mental factors were also predictors of the job performance of HSR dispatchers in this study is expected, which is consistent with results of other related occupations in previous studies [33,34,74]. Depression, as the most concerned mental health symptom, is associated with low self-esteem, reduced work motivation, and slower cognitive processing [33,75].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…at leads to the ability of multiobject tracking, becoming an important predictor of job performance just as the similar job of air traffic controllers [30]. e result that mental factors were also predictors of the job performance of HSR dispatchers in this study is expected, which is consistent with results of other related occupations in previous studies [33,34,74]. Depression, as the most concerned mental health symptom, is associated with low self-esteem, reduced work motivation, and slower cognitive processing [33,75].…”
Section: Discussionsupporting
confidence: 91%
“…In addition to cognitive abilities, a series of studies showed that mental health also impacts job performance. In the field of traffic safety, drivers with mental problems have much worse driving performance in both simulator and road tests, for depression and anxiety could slow down reaction speed and increase accident rates [33][34][35]. Similar results have also been found in nurses and operating workers [36,37].…”
Section: Introductionmentioning
confidence: 70%
“…These findings raise the question of whether mental status would be the cause or the result of the RTC. Evidence is growing that has examined rates of RTCs and traffic violations for drivers with mental illnesses, while other studies have examined the performance of people with mental illnesses on driving simulators [29]. Drivers who reported feeling depressed were more than twice as likely to be at fault for their collision than drivers who did not report such feelings.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, deficits in executive functions appear to increase with each depressive episode and persist after symptom remission [75]. The signature of cognitive impairment in depressed older patients with early-onset bipolar disorder also depicts mainly executive dysfunction [76].…”
Section: Depressionmentioning
confidence: 99%